Is the Sanctity of Contract Cast in Stone? An Evaluation of AB v Pridwin Preparatory School - Laubscher, Michael (Obiter, 2020)
This matter involves an appeal by AB (father) and CB (mother) (parents of DB and EB) against a decision of the South Gauteng High Court. The High Court found that the decision of the first respondent (Pridwin Preparatory School) to terminate a contract that had been concluded between it and the appellants was constitutional and acceptable, and thus found in favour of the respondents. This meant that the two children had to find another school to attend. The school based its action on a termination clause in paragraph 9.3 of the contract that had been concluded between the parties.The appellants (AB and CB) failed to gain direct access to the Constitutional Court1 and were granted leave to approach the Supreme Court of Appeal (AB v Pridwin Preparatory School (1134/2017) [2018] ZASCA 150; [2019] 1 All SA 1 (SCA); 2019 (1) SA 327 (SCA) (1 November 2018). This discussion focuses on the Supreme Court of Appeal judgment. The appeal was dismissed with costs, four of the five judges concurring, and one judge, Mocumie JA, offering a dissenting judgment.Five respondents were cited in this appeal: Pridwin Preparatory School, its principal (Mr Marx), the school’s board, the Gauteng Education Department, and the Independent Schools Association of Southern Africa.The appellants based their appeal on various grounds. Their fundamental argument rested on the claim that the termination clause that the school relied on was unconstitutional for various reasons, which meant that the school had no right to exclude the two children from attending the said school.The appellants argued that: the school had a constitutional obligation to act reasonably and afford the appellants a hearing before cancelling the contracts; the school did not adhere to the Promotion of Administrative Justice Act (3 of 2000 (PAJA)); and the contract (specifically the termination clause invoked by the school) was unconstitutional based on public policy (par 2 of the judgment).